Efektivitas pelaksanaan kebijakan sistem kelas tuntas berkelanjutan di kabupaten Gowa - Harakan, Ahmad (Universitas Muhammadiyah Ponorogo, 2017)
Education becomes complicated problems of the nation, Â the implementation of the teaching and learning process requires output at improving the quality of human development. Responding to the current educational facts, the Gowa local government policies to innovate to present Sistem Kelas Tuntas Berkelanjutan. By using a qualitative approach and type of phenomenology, and descriptive. Interviews and direct observation in data collection has answered problems related to the effectiveness of education policies sector and implemented by the Local Government of Gowa. Innovative and creative, support and satisfaction of the people, as well as the maximal of implementation of the policy be an indicator of the effectiveness of policies initiated by the LocalÂ Government of Gowa